Experience in the Management of Patients with Acute Type A Aortic Dissection and Coronary Ostial Involvement Classified as Neri Type B - Oleh I. Sarhosh; Vitalii I. Kravchenko; Ihor I. Zhekov; Ivan M. Kravchenko; Oleksandr M. Dovgan (Український журнал серцево-судинної хірургії)
Introduction. Acute type A aortic dissection (ATAAD) is a life-threatening condition with a high mortality rate, particularly in the absence of surgical intervention. Coronary artery involvement in ATAAD occurs in 7–20.7% of patients and is associated with a poor prognosis. Despite various surgical approaches, the optimal treatment strategy remains controversial, especially in cases of type B coronary ostial dissection according to the Neri classification.